Pengaruh Ice Breaking terhadap Model Pembelajaran Problem Based Learning dalam Meningkatkan Minat dan Hasil Belajar Peserta Didik SMK Negeri 3 Malang - Gidion Aldi; Satrio Hadi Wijoyo; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Based on the results of observations and interviews conducted by researchers at SMK Negeri 3 Malang, there are problems in the form of student learning interests that are not marked by the need to be given a stimulus at the beginning of learning, learning methods and models that have not been able to increase students' interest in learning. Based on these problems, this study aims to determine the influence of the use of Ice Breaking on the Problem Based learning in increasing the interest and learning outcomes of students at SMK Negeri 3 Malang. The research method uses Quasi Experimental with a Nonequivalent Control Group Design. Experimental research populations of class TKJ 1 and TKJ 2 SMK Negeri 3 Malang. The research sample was class X TKJ 1 35 students and X TKJ 2 35 students. Data collection techniques are carried out by observation, questionnaires and interviews. The tests carried out include testing for normality, homogeneity, differences in pretest, differences in posttest, improvement of pretest and posttest of both classes and Effect Size. The test aims to determine whether Ice Breaking has an effect on the Problem Based learning in increasing the interest and learning outcomes of students.